The Changing of ‘Sor Singgih Basa’ in Balinese Root Based on the Internal Modification: Morpho-Phonology Study - Okasunu, I Gusti Ayu Sundari; Dewi, Komang Yuly Sintia; Udayana, I Nyoman (Universitas Sanata Dharma, 2023)
This research investigates the relationship between phonology and morphology in influencing the changing Balinese speech level, namely ‘singgih’ (high) and ‘sor’ (low). The analysis focuses on utilizing the internal modification of a formal morphological element (root) in Balinese that creates a pattern of alternation apophony for vowel and consonant mutation, which lead to the transformation of speech level. Qualitative data analysis, including internal structure diagrams and observation, is used to analyze the data. There are 54 words found in the data findings using the documentation method from Balinese dictionary. The analysis results are (1) the alternate vowels and the mutation of consonant distinguished the level of the word without changing the meaning; (2) most of the alternation vowels change from [+low, +back] vowel into [+high] vowel, namely umlaut process; (3) the consonant mutation corresponds with the phonological sets of the consonant in initial position or phoneme addition in the middle position. Thus, this study has enriched and enlarged the linguistics documentation for the umlaut and ablaut existence in the Austronesian language.